Influence of various stressors on the expression of core genes of the small interfering RNA pathway in the oriental fruit fly, Bactrocera dorsalis. (25th May 2016) - Xie, Yi‐Fei; Niu, Jin‐Zhi; Jiang, Xuan‐Zhao; Yang, Wen‐Jia; Shen, Guang‐Mao; Wei, Dong; Smagghe, Guy; Wang, Jin‐Jun
Abstract: RNA interference (RNAi)‐based technology has emerged as a potential tool for controlling insect pests, however, previous studies found that the efficiency of RNAi in Bactrocera dorsalis was variable. In nature, insects often meet various challenges, such as pathogen infections, extreme temperatures, lack of nutrition and heavy metals. To better understand the association of the stressors with efficiency of RNAi, in the current study we tested the expression of three core genes, dicer2 ( Bddcr2 ), r2d2 ( Bdr2d2 ) and argonaute2 ( Bdago2 ), of the small interfering RNA (siRNA) pathway of B. dorsalis upon various stressors. Our results showed that all three genes were upregulated by the infection of invertebrate iridescent virus 6, which suggested a function of the siRNA pathway against viral infection. The loading of FeCl3 could also increase the expression of Bddcr2 . The treatments of Escherichia coli, extremely high (40°C) and low (0°C) temperatures, as well as starvation, could negatively influence the expression of Bddcr2 and/or Bdago2 . In total, our results showed that various stressors could influence the expression of core components of B. dorsalis siRNA pathway. This highlights further speculation on the RNAi efficiency upon these stressors. Considering the complexity and variation of RNAi efficiency in different conditions, these results provide initial aspects in possible environmental stressors to influence the activity of the siRNA pathway, but the real impact of RNAi efficiency posed by these stressors requires further studies.